2013
DOI: 10.1111/cen.12247
|View full text |Cite
|
Sign up to set email alerts
|

Goitre and urinary iodine excretion survey in schoolchildren of Kashmir Valley

Abstract: The marked improvement in overall iodine nutrition in Kashmir Valley- one and a half decades after implementation of salt iodization should encourage healthcare providers to make tangible efforts for implementation of iodization programmes in areas with iodine deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
7
1
1
Order By: Relevance
“…While the females outnumbered the males in the present study, the proportion was less than that reported in the other studies (4,16). This could be the result of the improved iodine status of the population (11), following the universal iodization program and a consequent increase in the tendency for autoimmune disorders (18), which might have ultimately resulted in a lower female to male ratio. Moreover, ethnic variation, regional differences, and/or poor accessibility to medical facilities among females due to various socio-religious factors might also explain the lower female to male ratio.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…While the females outnumbered the males in the present study, the proportion was less than that reported in the other studies (4,16). This could be the result of the improved iodine status of the population (11), following the universal iodization program and a consequent increase in the tendency for autoimmune disorders (18), which might have ultimately resulted in a lower female to male ratio. Moreover, ethnic variation, regional differences, and/or poor accessibility to medical facilities among females due to various socio-religious factors might also explain the lower female to male ratio.…”
Section: Discussioncontrasting
confidence: 78%
“…The Kashmir Valley, located in the North-Indian Union territory of Jammu and Kashmir, has been a known iodine-deficient area (10). With the universal implementation of salt iodization, a marked improvement in the overall iodine nutrition was observed in the Kashmir Valley (11). It is well known that the incidence of hyperthyroidism, including GD, may increase after salt iodization (12).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Goiter was found to be a mild public health issue in areas of Champaran and Bharatpur by Umesh Kapil where the prevalence were 7.2% and 11.6% respectively. 11,12 Other studies with similar findings were seen in Uttarakhand where the total goiter rate was 13.2% and 17% in Faridabad as observed by Lohiya et al 13,14 The reason for this broad variation in prevalence can be because of the demographic characteristics in our country which influence the prevalence of goiter. 15 This could also be due to variation in the methodology adopted in terms of sample size and age groups included in various studies.…”
Section: Prevalence Of Goitersupporting
confidence: 71%
“…Anak usia sekolah merupakan kelompok yang tepat untuk penilaian kekurangan iodium karena kerentanan fisiologis yang tinggi dan keterjangkauan anak sekolah untuk diperiksa. 11 Garam yang digunakan di wilayah penelitian pada umumnya menggunakan garam berbentuk halus dan bata. Berbeda dengan penelitian di Kabupaten Semarang bahwa secara keseluruhan, hampir semua (97 persen) keluarga menggunakan garam bentuk bata.…”
Section: Pembahasanunclassified